Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Jasa Kapal Pada PT. Tirta Permai Bahari Medan - Charisma Kuriata Ginting; Tatia Kristina Br Tambunan; Putri Ramadania; Samuel Tenang Ukur Ardianta Ginting (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2026)
Indonesia is an archipelagic country with maritime economic activities, which include port management, ship docking, cargo transportation, and various shipping-related services. Therefore, many shipping companies operate in the field of ship agency services. Their operational activities, including ship arrivals and departures, raise concerns about service quality and customer satisfaction. The independent variable (X) is Service Quality, and the dependent variable (Y) is Customer Satisfaction. The method used is quantitative descriptive analysis. The results of a simple regression analysis conclude that variable X can influence variable Y, as seen from the magnitude of the regression coefficient obtained. The results of the multiple correlation (R) test indicate that each increase in variable X will increase variable Y. The results of the multiple determination coefficient test indicate that the independent variable influences the dependent variable, while the remaining variables are influenced by other variables. The partial coefficient (r) test results show a regression coefficient of 61.6% and an R-square of 37.9%, which will determine the extent to which the independent variable dominates the dependent variable. The theories are then tested through measuring variables from numbers and analyzing data using statistical procedures using SPSS software. Based on this, the research objective and title are